Formalizing the Informal: Adopting a Formal Culture-Fit Measurement System in the Employee-Selection Process - Cai, Wei (The Accounting Review, 2023)
ABSTRACT Many organizations rely on formal management control systems that align employee values with organizational values (i.e., culture fit) to shape organizational culture. Using proprietary data from a highly decentralized organization, I examine employee-performance consequences of adopting a formal culture-fit measurement system in employee selection. I exploit the staggered feature of the adoption of the system and find that employees selected with the system perform significantly better than those without the system. However, the performance consequences of adopting the culture-fit measurement system exhibit significant variation, depending on (1) alignment of existing local culture and organizational values and (2) noise in the measurement of culture fit due to applicants’ gaming behavior. Taken together, this study implies that the adoption of a formal culture-fit measurement system can potentially alleviate difficulties in instilling organizational values and highlights the conditions under which such a system can be more effective in facilitating the diffusion of organizational culture.